HUBUNGAN SIKAP, NORMA SUBYEKTIF DAN PERSEPSI KENDALI PERILAKU TERHADAP NIAT KTH DALAM BUDIDAYA TANAMAN ENERGI DI YOGYAKARTA - Adi Nugroho; Ahdiar Fikri Maulana; Singgih Utomo; Silvi Nur Oktalina; Prasetyo Nugroho; Wiyono Wiyono (Lambung Mangkurat University-Indonesia, 2021)
Energy policy in the world has changed due to the climate crisis. As a result, the need for renewable energy supply is increasing. Trees in the forestry sector are a reliable source of biomass for renewable energy production. Community forests could play an important role in supplying biomass-based renewable energy production. The study aims to understand the attitude, subjective norms, and perceived behavioural control on Farmers Forest Group's intention in cultivating trees for energy in Yogyakarta Province. The Theory of Planned Behaviour approach was used to analyse the correlation between Attitudes, Subjective Norms, and Perceived Behavioural Control on Forest Farmers Group Intention in cultivating trees for renewable energy. A survey using an online questionnaire was conducted on Forest Farmers Groups in four districts in DI Yogyakarta; Sleman, Kulonprogo, Bantul, and Gunungkidul. The survey results were analysed using non-parametric statistics.The results showed a significant positive correlation between Attitudes, Subjective Norms, and Perceived Behavioural Control on the Forest Farmers Group's Intention to cultivate trees for renewable energy. The study provides policymakers and privates with insight into working with the farmers when they are about to implement biomass-based renewable energy programs